Sr/Ca, Mg/Ca and Ba/Ca Ratios in the Otolith of Sea Bass in Peninsular Malaysia as salinity influence markers - Afiza Suriani Sarimin,; Che Abd Rahim Mohamed, (Universiti Kebangsaan Malaysia, 2014)
The otoliths of sea bass (Lates calcarifer) were sampled from 23 locations in Peninsular Malaysia in order to analyse the Sr/Ca, Mg/Ca and Ba/Ca ratios. This study found that these elements/Ca ratios in sea bass otoliths were correlated with the salinity zone (thalassic series) compared with elements/Ca ratios in ambient water. The contradictory pattern of Sr/Ca ratios and Ba/Ca ratios in otoliths was found according to salinity zone variations. Thus, oligohaline waters showed the highest Ba/Ca ratios while the highest Sr/Ca ratios were recorded for saline waters. The terrigenous enrichment of Ba in water also affects the Ba content in otoliths. The presence of Mg in otoliths acts as a rival to Ba, thus affecting Mg and Ba deposition. Meanwhile, Ba is the tracer for salinity fluctuations based on the partition coefficient (D) and it shows significant changes. However, the elements in otoliths were found to originate indirectly from the water column. The sequence of the elements/Ca ratios in otoliths and ambient water was Sr/Ca>Mg/Ca>Ba/Ca and Sr/Ca>Ba/Ca>Mg/Ca, respectively.